Μ-Pseudo-Almost Automorphic Solutions for some Differential Equations with Reflection of the Argument. (4th March 2017) - Miraoui, Mohsen
ABSTRACT: From the fixed-point methods and the properties of the μ -pseudo-almost automorphic functions, the existence and uniqueness of measure pseudo-almost automorphic solution are obtained for differential equations involving reflection of the argument.